Nursing Genetics and Genomics Education in Indonesia: Philosophy and Ethics Study (a Hermeneutics Approach) - Woitila Wangi, Karolus Yosef; Sakinah, Innama; Ningsih, Dewi Andariya; Vanawati, Noviana; Adiningsih, Dian; Simatupang, Erna Juliana (KnE Life Sciences, 2021)
This study was conducted to provide a philosophical and ethical description of the development of genetics and genomics nursing science and the importance of its incorporation into nursing education in Indonesia. Researchers have adopted five of the seven steps of the Heideggerian hermeneutics. All data has been obtained from literature research. The qualitative analysis of secondary data has applied the data analysis. The Coherence theory of truth criteria has been applied to maintain the consistency of scientific truth. The consistent statement system has used the principle of logic as a guide to interpreting the facts and opinions of others adequately. Nursing genetics and genomics is an ethical, philosophical product of nursing science development and a new scope of science as an adaptation to global health issues. The areas of science in nursing need to be developed further by placing genetics and genomics issues that can be adapted into the curriculum of the nursing higher education curriculum in Indonesia. Keywords: Education; Ethics; Genetics; Genomics; Philosophy